The Routledge companion to mobile media - Goggin, Gerard 1964-.; Hjorth, Larissa (New York Routledge, 2017)
"The last decade has witnessed the rise of the cell phone from a mode of communication to an indispensable multimedia device, and this phenomenon has led to the burgeoning of mobile communication studies in media, cultural studies, and communication departments across the academy. The Routledge Companion to Mobile Media seeks to be the definitive publication for scholars and students interested in comprehending all the various aspects of mobile media. This collection, which gathers together original articles by a global roster of contributors from a variety of disciplines, sets out to contextualize the increasingly convergent areas surrounding social, geosocial, and mobile media discourses. Features include:comprehensive and interdisciplinary models and approaches for analyzing mobile media; wide-ranging case studies that draw from this truly global field, including China, Africa, Southeast Asia, the Middle East, and Latin America, as well as Europe, the UK, and the US; a consideration of mobile media as part of broader media ecologies and histories; chapters setting out the economic and policy underpinnings of mobile media; explorations of the artistic and creative dimensions of mobile media; studies of emerging issues such as ecological sustainability; up-to-date overviews on social and locative media by pioneers in the field. Drawn from a range of theoretical, artistic, and cultural approaches, The Routledge Companion to Mobile Media will serve as a crucial reference text to inform and orient those interested in this quickly expanding and far-reaching field"-- Provided by publisher.
Introduction: Mobile Media Research - State of the Art -- Part I: Fields of Mobile Media: Observing mobile multimedia - Understanding the role of mobile media in society: models and theories - Theorizing mobile communication in the intimate sphere - Localizing mobile media: a Philippine perspective - Mobile locative media: the nexus of mobile phones and social media -- Part II: Infrastructures, Economics, and Policies: Structure of mobile telecommunications markets: operators - Next generation mobile networks and technologies: impact on mobile media - Mobile media and next generation broadband: policy and markets - The democratization of internet access through mobile adoption in Latin America - Informal mobile economies -- Part III: New and Old Media and Entertainment: Small, cheap, and out of control: reflections on the transistor radio - The production and consumption of news in an age of mobile media - Mobile video: spreading stories with mobile media - A decade of mobile moving-image practice - The smartphone app economy and app ecosystems - Feeding digital omnivores: the impact of mobile meda in digital entertainment -- Part IV: Arts of Mobile Media: Mobile art: out of your pocket - Arte.mov, Mobilefest and the emergence of a mobile culture in Brazil - Genealogy of mobile creativity: a media archaeological approach to literary practice in Japan - Does mobile matter? The case of one-off reading - Learning with mobile phones - Mobile media photography - Mobile games: from Tetris to Foursquare - Paying attention to Angry Birds: rearticulating hybrid worlds and embodied play through casual iPhone games -- Part V: New Social Categories, Identities, and Practices: Ageing mobile media - The social in the mobile: QQ as cross-generational media in China - Children and the mobile internet - The emotional identity of the mobile phone - Mobile media in the emotional and moral economies of the household - Bricks, spies, and shoe phones: researching mobile media in work and professional life - Mobilities and race - Women, "Double Work," and mobile media: the more things change, the more they stay the same - The use of mobile media and the struggle for women's empowerment - Masculinity, sport, and mobile phones: a case study of surfing - Tactics of well-being: mobile media and a new turn in the human-food relationship - Mobile sentimental education: attachment, recognition, and modulations of intimacy -- Part VI: Cultures and Politics: Mobile communication and civic life: implications of private and public uses of the technology - Political communication, the internet, and mobile media: the case of Passion Times in Hong Kong - Mobile ensembles: the uses of mobile phones for social protest by Spain's Indignados - Locating labor in mobile media studies - Pavement internet: mobile media economies and ecologies in South Africa - The aesthetics of mobile money platforms in Haiti -- Part VII: Geographies of Mobile Social Media: Mobile phone usage in Turkana, Kenya - The digital wayfarer: reconceptualizing camera phone practices in an age of locative media - Intimate banalities: the emotional currency of shared camera phone images during the Queensland Flood Disaster - Mobile media, place, and location - Storytelling with mobile media: exploring the intersection of site-specificity, content, and materiality
Includes index.
Prof. Ma. Theresa Tabada (Recommending faculty) - Bookfair2017
Includes bibliographical references and index.
Keywords: Mobile communication systems; Cell phone systems; Multimedia communications; Mobile communication systems -- Social aspects; Cell phone systems -- Social aspects; Multimedia communications -- Social aspects; Mobile communication systems -- Economic aspects; Cell phone systems -- Economic aspects; Multimedia communications -- Economic aspects